1983
DOI: 10.1139/z83-123
|View full text |Cite
|
Sign up to set email alerts
|

Hematology distinguishes coastal and offshore forms of dolphins (Tursiops)

Abstract: Bottlenose dolphins, Tursiops truncatus, can be separated into coastal and offshore ecotypes based upon hemoglobin levels, packed cell volumes, and red blood cell counts, the offshore form having higher values for all three measures. Captive-bred crosses between coastal and offshore types produce animals with intermediate hematologic profiles suggesting a significant genetic basis for these differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 2 publications
1
58
0
1
Order By: Relevance
“…An alternative explanation is that we made use of electrospray ionization mass spectrometry for sample evaluation, which is much more sensitive to mass differences than are assays based on electrophoretic mobility, where species with charge differences are most readily detected. In the previous studies, results of electrophoretic analysis led to the conclusion that offshore populations of T. truncatus typically have two types of Hbs, while coastal populations of bottlenose dolphins have only one Hb (Duffield et al, 1983;Hersh and Duffield, 1990). The latter authors point out that interbreeding has occurred in aquarium settings between offshore and coastal dolphins and that "intermediate" Hb patterns have been observed in the offspring of such pairings.…”
Section: Structural Heterogeneity Among Bottlenose Dolphin Hb Samplesmentioning
confidence: 97%
See 3 more Smart Citations
“…An alternative explanation is that we made use of electrospray ionization mass spectrometry for sample evaluation, which is much more sensitive to mass differences than are assays based on electrophoretic mobility, where species with charge differences are most readily detected. In the previous studies, results of electrophoretic analysis led to the conclusion that offshore populations of T. truncatus typically have two types of Hbs, while coastal populations of bottlenose dolphins have only one Hb (Duffield et al, 1983;Hersh and Duffield, 1990). The latter authors point out that interbreeding has occurred in aquarium settings between offshore and coastal dolphins and that "intermediate" Hb patterns have been observed in the offspring of such pairings.…”
Section: Structural Heterogeneity Among Bottlenose Dolphin Hb Samplesmentioning
confidence: 97%
“…Many studies have reported that these organisms have higher than typical vertebrate levels of blood volume, Hb concentrations, hematocrit, and myoglobin concentrations (Ridgway and Johnston, 1966;Bryden and Lim, 1969;Elsner, 1969;Kooyman et al, 1980;Vogl and Fisher, 1982;Cornell, 1983;Duffield, Ridgway and Cornell, 1983;Snyder, 1983;Kanwisher and Ridgway, 1983;Ridgway et al, 1984;Qvist et al, 1986;Hedrick, Duffield and Cornell, 1986;Kooyman, 1986).…”
Section: Ecotypes Of Bottlenose Dolphinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences between nearshore and offshore populations have been found for this species in many geographic locations 4 (Ross, 1977;1984;Duffield et al, 1983;Ross and Cockroft, 1990;Van Waerebeck et al, 1990;Mead and Potter, 1995;Hoelzel et al, 1998). This great geographical variation has led some authors in the past to divide the genus Tursiops into as many as 20 different species (Hershkovitz, 1966;Rice, 1998).…”
Section: Introductionmentioning
confidence: 98%